The scale-up gap - Fratto, Chiara,Gatti, Matteo,Kivernyk, Anastasia,Sinnott, Emily,Van Der Wielen, Wouter (European Investment Bank, 2024)
Closing the scale-up financing gap is essential for the European Union to maintain its edge in technology. Scale-ups are young, medium-sized firms with high growth potential, more productive than the average company and leader in the development of new technologies. This report provides new evidence on the financial constraints faced by companies as they enter the crucial scale-up phase. The analysis follows firms that received venture capital backing and reached the scale-up phase in the European Union after 2013. By tracking these firms over time, the report examines the financing they receive and the investors they attract. The report also documents the link between financial constraints and firms' outcomes, including relocations and likelihood to exit via initial public offering or acquisition. Addressing the scale-up gap requires the removal of investment barriers, including making advancements in deepening capital markets, particularly the venture capital market, and targeted public interventions to jump start the market.
10.2867/382579
Keywords: Graue Literatur; size of business; financial market; venture capital; innovation; investment; entrepreneurship; new technology; corporate finance; company growth; financing